2021
DOI: 10.1111/and.14281
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccination is associated with a decreased risk of orchitis and/or epididymitis in men

Abstract: Vaccine hesitancy is a major public health obstacle to fighting the ongoing COVID‐19 epidemic. Due to studies that show COVID‐19 infection can affect sperm parameters and lead to orchitis, the public are concerned about the effect of the COVID vaccines on male reproduction. In this study, we investigated the association between COVID‐19 vaccination and risk of developing orchitis and/or epididymitis outcomes in a cohort of men using a large, US‐based, electronic health record database. After balancing for conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 10 publications
(10 reference statements)
1
27
0
2
Order By: Relevance
“…As regards the two studies which detected viral RNA in sperm samples, the international debate has highlighted specific methodological errors made in the two studies [16,72]. In contrast to these studies, comparisons of semen parameters taken before and after men were vaccinated found that corona vaccines had no negative impact on male fertility [74,75,83]. However, male fertility was found to be at least temporarily impaired after SARS-CoV-2 infection, particularly in severe cases of disease, with more than one third of studies showing a deterioration of all 3 relevant semen parameters.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As regards the two studies which detected viral RNA in sperm samples, the international debate has highlighted specific methodological errors made in the two studies [16,72]. In contrast to these studies, comparisons of semen parameters taken before and after men were vaccinated found that corona vaccines had no negative impact on male fertility [74,75,83]. However, male fertility was found to be at least temporarily impaired after SARS-CoV-2 infection, particularly in severe cases of disease, with more than one third of studies showing a deterioration of all 3 relevant semen parameters.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 663 774 men who had received at least one vaccination were compared with 9 985 154 men who were not vaccinated. Orchitis and/or epididymitis occurred significantly less often in men who had been vaccinated (OR = 0.568; 95% CI: 0.497 – 0.649; p < 0.0001) 83 .…”
Section: Corona Vaccinationmentioning
confidence: 93%
See 1 more Smart Citation
“…In a US database study of 663 775 men, Carto et al. revealed that men vaccinated against COVID‐19 had 43.2% decreased odds of being diagnosed with epididymo‐orchitis [ 8 ].…”
mentioning
confidence: 99%
“…
We would like to correspond and give our ideas on the publication by Carto et al (2021). Carto et al ( 2021) noted that COVID-19 vaccine recipients, either complete or incomplete all doses, had a decreased risk of getting illness from epididymitis and orchitis after vaccination.
…”
mentioning
confidence: 99%